A NOVEL APPROACH TO STATE SPACE TIME DOMAIN AUTOREGRESSIVE SIGNAL PROCESSING USING OPTIMAL RECURSIVE ESTIMATOR - A, Jawahar; P, Murali Krishna; Ss, Kiran (Innovare Journal of Engineering and Technology, 2018)
This work describes the concept of filtering of signals using discrete Kalman filter. The true state of constant, random constant having process noise and autoregressive (p) process when corrupted by measurement noise are estimated using discrete Kalman filter and results are presented using MATLAB.